2022
DOI: 10.1088/1361-6528/ac4679
|View full text |Cite
|
Sign up to set email alerts
|

A grease for domain walls motion in HfO2-based ferroelectrics

Abstract: A large coercive field EC of HfO2 based ferroelectric devices poses critical performance issues in their applications as ferroelectric memories and ferroelectric field effect transistors. A new design to reduce EC by fabricating nanolaminate Hf0.5Zr0.5O2 / ZrO2 (HZZ) thin films is used, followed by an ensuing annealing process at a comparatively high temperature 700 °C. High-resolution electron microscopy imaging detects tetragonal-like domain walls between orthorhombic polar regions. These walls decrease the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recently, Kashir et al observed a substantial decrease in E C upon the introduction of tetragonal‐like domain walls. [ 405 ] A considerable increase in dielectric permittivity at domain walls confirmed the higher mobility, which was supposed to be the cause of the reduction in E C . [Correction added after publication 09 June 2022: Figure 20 changed to Figure 21 in preceding paragraph]…”
Section: Challenges Of Hfo2 In Emerging Nonvolatile Memory Devicesmentioning
confidence: 99%
“…Recently, Kashir et al observed a substantial decrease in E C upon the introduction of tetragonal‐like domain walls. [ 405 ] A considerable increase in dielectric permittivity at domain walls confirmed the higher mobility, which was supposed to be the cause of the reduction in E C . [Correction added after publication 09 June 2022: Figure 20 changed to Figure 21 in preceding paragraph]…”
Section: Challenges Of Hfo2 In Emerging Nonvolatile Memory Devicesmentioning
confidence: 99%
“…These simulations inspired the synthesis of alternating polar/nonpolar Hf 0.5 Zr 0.5 O 2 /ZrO 2 nanolaminates where formation of a nonpolar phase at domain walls acts as a “grease” to increase domain‐wall mobility, ultimately resulting in a 40% decrease in the coercive field. [ 334 ] Further work combining theory and experiment on these unconventional ferroelectrics will be essential in addressing problems of high coercive fields and poor fatigue resistance typical of ferroelectric HfO 2 ‐ and ZrO 2 ‐based materials, yet the demonstration of switchable polarization in a material amenable to current industry processes is promising for its near‐future integration into novel ferroelectric devices.…”
Section: New Materials and Epitaxymentioning
confidence: 99%
“…It is possible to change the polarization direction, thus maintaining quasi-chirality at the interface between the o-phase and t-phase owing to the effect of the topological domain wall [11]. Therefore, the existence of ultra-thin t-phase like spacer in ferroelectric films is a key to the reduction of the switching barrier without causing a detrimental degradation of polarization properties [12].…”
Section: Introductionmentioning
confidence: 99%